Whole-Exome Sequencing Identifies a Novel Variant (c.1538T > C) of TNNI3K in Arrhythmogenic Right Ventricular Cardiomyopathy - Xie, Ting; Yang, Yifeng; Gong, Ke; Luo, Yong; Guo, Hui; Liu, Ruilin; Wang, Lei; Tan, Zhiping; Luo, Jinwen; Xie, Li (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds: Arrhythmic right ventricular cardiomyopathy (ARVC) is a cardiomyopathy with a genetic predisposition that can lead to sudden cardiac death and heart failure. According to the 2010 Task Force Criteria, genetic diagnosis is one of the most important methods, but so far few genes related to ARVC have been identified. Methods: In this study, the pathogenic gene of an ARVC patient was examined using whole exome sequencing. Plasmids of TNNI3K were constructed, and the effects of the TNNI3K variant was investigated by real-time polymerase chain reaction (PCR) and western blot. Results: A novel mutation (c.1538T > C) of TNNI3K was identified, with phenotypes of dominant right ventricular (RV) disease fulfilling ’definite’ diagnosis of ARVC according to the 2010 Task Force Criteria. A comprehensive assessment revealed that the mutation was pathogenic. We found that this mutation would lead to a decrease in the level of TNNI3K mRNA and protein, as well as a decrease in the expression of RYR2 gene, which further proves that TNNI3K plays an important role in cardiomyopathy and expands the spectrum of TNNI3K mutations. Conclusion: In this study, we reported TNNI3K mutation in ARVC for the first time, and the results not only contribute to the diagnosis of ARVC, but also provide a reference for genetic counseling and promote the understanding of the genetic mechanism of cardiomyopathy.